Leiomyoma of the Nasal Septum – A Case Report - Biswas, Binoy Krishna; Khan, Manjurul Karim; Jahan, Shahanaz (Community Based Medical Journal, 2024)
Leiomyomas of the nasal cavity are rare and benign tumour of vascular smooth muscle origin that uncommonly arise from the nasal septum. In the nasal cavity they contribute less than 1% of all human leiomyoma. Leiomyomas are more commonly found in female genital tract (uterus), gastrointestinal tract and subcutaneous tissue. They are classified in three groups: leiomyoma, angiomyoma and epithelioid leiomyoma. Here, we report a clinical case of a rare vascular leiomyoma in the nasal septum in a 32-year-old man. The treatment of choice was surgical excision. A brief review of the literature, treatment and aetiological variations are discussed. CBMJ 2024 July: vol. 13 no. 02 P: 274-276